Transferable, highly crystalline covellite membrane for multifunctional thermoelectric systems - Myungwoo Choi; Geonhee Lee; Yea‐Lee Lee; Hyejeong Lee; Jin‐Hoon Yang; Hanhwi Jang; Hyeonseok Han; MinSoung Kang; Seonggwang Yoo; A‐Rang Jang; Yong Suk Oh; Inkyu Park; et al. (InfoMat)
Abstract Emerging freestanding membrane technologies, especially using inorganic thermoelectric materials, demonstrate the potential for advanced thermoelectric platforms. However, using rare and toxic elements during material processing must be circumvented. Herein, we present a scalable method for synthesizing highly crystalline CuS membranes for thermoelectric applications. By sulfurizing crystalline Cu, we produce a highly percolated and easily transferable network of submicron CuS rods. The CuS membrane effectively separates thermal and electrical properties to achieve a power factor of 0.50 mW m−1 K−2 and thermal conductivity of 0.37 W m−1 K−1 at 650 K (estimated value). This yields a record‐high dimensionless figure‐of‐merit of 0.91 at 650 K (estimated value) for covellite. Moreover, integrating 12 CuS devices into a module resulted in a power generation of ~4 μW at ΔT of 40 K despite using a straightforward configuration with only p‐type CuS. Furthermore, based on the temperature‐dependent electrical characteristics of CuS, we develop a wearable temperature sensor with antibacterial properties.